2009
DOI: 10.1016/j.bbabio.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement of two homologous proteins encoded by sll1214 and sll1874 for the reaction of Mg protoporphyrin monomethylester oxidative cyclase under aerobic and micro-oxic growth conditions

Abstract: The two open reading frames in the Synechocystis sp. PCC 6803 genome, sll1214 and sll1874, here designated cycI and cycII, respectively, encode similar proteins, which are involved in the Mg protoporphyrin monomethylester (MgProtoME) cyclase reaction. The impairment of tetrapyrrole biosynthesis was examined by separate inactivation of both cyclase encoding genes followed by analysis of chlorophyll contents, MgProtoME levels and several enzyme activities of tetrapyrrole biosynthesis. We additionally addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…A reciprocal pulldown assay using FLAG-Ycf54 showed that Sll1214 is trapped as prey. The absence of Sll1874 in the FLAGYcf54 eluate is not so surprising bearing in mind the aerobic growth conditions used to prepare the culture of FLAG-ycf54 strain; Sll1874 is specifically expressed under micro-oxic conditions, and its level is probably minimal under atmospheric oxygen level (20,21). In contrast to the membrane-bound Sll1214/Sll1874, Ycf54 appears to be a rather hydrophilic protein (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A reciprocal pulldown assay using FLAG-Ycf54 showed that Sll1214 is trapped as prey. The absence of Sll1874 in the FLAGYcf54 eluate is not so surprising bearing in mind the aerobic growth conditions used to prepare the culture of FLAG-ycf54 strain; Sll1874 is specifically expressed under micro-oxic conditions, and its level is probably minimal under atmospheric oxygen level (20,21). In contrast to the membrane-bound Sll1214/Sll1874, Ycf54 appears to be a rather hydrophilic protein (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work had identified two genes in Synechocystis, sll1214 and sll1874, as acsF homologs that encode the membrane component of the MgPME cyclase (20,21). To identify their protein partners, we tagged the N termini of Sll1214 and Sll1874 in vivo with 3ϫFLAG and purified both proteins from detergent-solubilized membrane extracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). Deletion of the native CycIencoding gene (sll1214) was attempted in this acsF Rg+ background; a previous attempt to delete cycI in the wild type (WT) under oxic conditions proved unsuccessful (19). Full segregation of ΔcycI in acsF Rg+ was achieved (Fig.…”
Section: Rvi Gelatinosus Acsf Complements the Loss Of Cyci In Synechmentioning
confidence: 99%
“…The cyanobacterium Synechocystis sp. PCC 6803 (hereinafter Synechocystis) also contains two isoforms of AcsF, designated CycI and CycII (19). Constitutively expressed cycI encodes the sole AcsF protein responsible for cyclase activity under oxic conditions, with cycII expressed only under microoxic conditions (13); overexpression of cycII cannot rescue cyclase function under a range of O 2 tensions when CycI levels are depleted (19).…”
mentioning
confidence: 99%